Manager as leader: Role of a manager and their responsibilities / Nurul Farhani Zainuddin and Siti Norumiah Yaakob - Zainuddin, Nurul Farhani; Yaakob, Siti Norumiah (Faculty of Information Management, 2014)
What is the job as a manager? What do they do? What is their role in the workplace? What is their responsibility? The terms manager is always often known by the society, but however does anybody really what their role in the agencies or company is?